1985
DOI: 10.1111/j.1550-7408.1985.tb03048.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Biometric, and Morphogenetic Comparison of Two Closely Related Species, Stylonychia vorax and S. pustulata (Ciliophora: Oxytrichidae)1

Abstract: Differences in the morphology of Stylonychia vorax Stokes, 1885 and S. pustulata (Müller, 1786) Ehrenberg, 1838 recognizable in vivo are the shape, the ventral cirral pattern, the caudal cirri, and the mode of moving. The dorsal‐bristle complexes are distinguishable by the length of dorsal kinety four and the spaces among the pairs of basal bodies. When the ranges of variation of different populations and clones are compared by biometric analyses, S. vorax shows a relatively stable cortical pattern whereas in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 5 publications
2
30
0
Order By: Relevance
“…Sladecek et al (1981) and Wegl (1983) give different saprobic valencies (-6 4 --; -2 6 2 -) . Wirnsberger et al (1985a) . Sladecek et al (1981) and Wegl (1983) give different saprobic valencies for S. pustulata and S. notophora (--10 --; --7 3 -) .…”
mentioning
confidence: 99%
“…Sladecek et al (1981) and Wegl (1983) give different saprobic valencies (-6 4 --; -2 6 2 -) . Wirnsberger et al (1985a) . Sladecek et al (1981) and Wegl (1983) give different saprobic valencies for S. pustulata and S. notophora (--10 --; --7 3 -) .…”
mentioning
confidence: 99%
“…Sapra and Dass isolated cells of Stylonychia from the Okhla region (Delhi) of the River Yamuna [9] (OK site in the present study), which they identified as Stylonychia notophora Stokes, 1885 [5]. Subsequently, several authors also suggested that this was a misidentification and was a population of T. pustulata (Müller, 1786) Ehrenberg, 1835 [3,10,11].…”
Section: Discussionmentioning
confidence: 67%
“…In the present study, morphological, morphogenetic and molecular data for six populations nominally identified as S. notophora sensu Sapra and Dass, 1970 were analysed for intra-clonal and inter-population variations. Using this integrative approach, comparisons between S. notophora sensu Sapra and Dass, 1970 [9] and T. pustulata [11] confirm that these taxa are identical. Therefore, S. notophora sensu Sapra and Dass, 1970 is a misidentification and is, in fact an Indian population of T. pustulata.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases, the oral primordium is curved rightwards and originates de novo [vs. originates adjacently (parakinetal?) to postperistomal cirri row in the European P. weissei (Wirnsberger et al, 1985)]; the undulating membranes start disaggregation before fusing; about half of the membranelles of the lapel are replaced; and the two rightmost FVT primordia originate from a primordium growing within the rightmost ventral row, which then splits in two.…”
Section: Discussionmentioning
confidence: 99%